PERAN INVESTASI MODAL FISIK DAN MODAL MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI KOTA PEKANBARU - mustika puspa rani; syapsan syapsan; dahlan tampubolon (Universitas Lancang Kuning, 2021)
This study aims to provide empirical evidence of the role of physical capital and human capital on economic growth. The contribution is focused on Pekanbaru City because it is the center of economic activity in Riau Province, so it is necessary to analyze the contribution of physical and human capital development to regional economic growth. This study uses multiple linear regression analysis in Pekanbaru City during the 2009-2018 period. The asset capital indicators used in this research are fixed assets that have been realized for the last 10 years, and the human capital used in this study is the average length of schooling of the population for the education level and thelife expectancy of the population for the health level. The estimation results show that the level of education has a positive and significant contribution to economic growth in Pekanbaru City. This indicates the important role of education as one of the main sources to achieve better economic development. Another finding from this study is that fixed asset capital has a negative and significant effect on economic growth in Pekanbaru City, this is caused by the use of fixed assets in not being fully utilized for activities that can encourage productivity activities in Pekanbaru City.